Pro-inflammatory cytokines: Useful markers for the diagnosis of canine mammary tumours?. (April 2016) - Andaluz, Ana; Yeste, Marc; Rodríguez-Gil, Joan E.; Rigau, Teresa; García, Félix; Rivera del Álamo, Maria Montserrat
Highlights: Expression of 60 cytokines was evaluated in healthy and neoplastic canine mammary glands. Mammary tumours show higher expression of CKβ-8-1, EGF, NAP-2 and PARC than healthy mammary tissue. Malignant mammary tumours show higher expression of MCP-1, MCP-2, PDGF-BB, RANTES and SCF than benign mammary tumours. Evaluating a proper combination of cytokines could provide a more accurate diagnostic of tumours in canine mammary glands. Abstract: The aim of the present study was to analyse the expression of 60 pro-inflammatory cytokines as possible markers of malignancy in canine mammary tumours using a human cytokine antibody array. The cytokines were grouped into two different categories: (1) cytokines in which expression indicated the presence of a mammary tumour and (2) cytokines in which expression differentiated between simple mammary adenoma, tubulopapillary carcinoma or complex carcinoma. These data suggest that specific pro-inflammatory cytokines could be useful as tools for the diagnosis of canine mammary tumours.